2015
DOI: 10.1111/jdv.13305
|View full text |Cite
|
Sign up to set email alerts
|

Brimonidine gel 0.33% rapidly improves patient‐reported outcomes by controlling facial erythema of rosacea: a randomized, double‐blind, vehicle‐controlled study

Abstract: BackgroundFacial redness contributes to impaired psychosocial functioning in rosacea patients and the only approved treatment for erythema is topical brimonidine gel 0.33%.ObjectivesTo evaluate patient‐reported outcomes, as well as efficacy and safety, in subjects with self‐perceived severe erythema treated with brimonidine gel 0.33% compared to vehicle.MethodsAn 8‐day multicenter, randomized study comparing once‐daily brimonidine gel 0.33% with vehicle gel using a facial redness questionnaire, subject satisfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 14 publications
1
28
0
5
Order By: Relevance
“…[2] Several clinical studies have demonstrated that brimonidine rapidly improves facial flushing and erythema. [2,3] However, the molecular and histological effects of brimonidine on rosacea remain largely unknown. Although the vasoconstrictive property of brimonidine gel has been suggested to contribute to the therapeutic effect, it was assumed that not only contracting the expanded blood vessels would act on the therapeutic mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Several clinical studies have demonstrated that brimonidine rapidly improves facial flushing and erythema. [2,3] However, the molecular and histological effects of brimonidine on rosacea remain largely unknown. Although the vasoconstrictive property of brimonidine gel has been suggested to contribute to the therapeutic effect, it was assumed that not only contracting the expanded blood vessels would act on the therapeutic mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…An 8‐day multicenter, randomized study comparing once‐daily brimonidine 3 mg/g gel with vehicle gel proved that brimonidine allows patients with self‐perceived severe erythema to rapidly control their facial redness. In addition, brimonidine significantly improved patient‐reported outcomes in the treatment of persistent facial erythema of rosacea .…”
Section: Approved Topical Therapiesmentioning
confidence: 96%
“…Daher kann eine adäquate Behandlung der persistierenden Gesichtsröte die Lebensqualität verbessern [ 21,22 ] . So konnte in einer 8-tägigen multizentrischen, randomisierten Studie, in der Brimonidin 3 mg/g Gel mit einem Vehikel-Gel verglichen wurde, erwiesen werden, dass Patienten mit einem von ihnen selbst als schwer eingestuftes Erythem mit Hilfe von Brimonidin ihre Gesichtsröte schnell unter Kontrolle bringen konnten [ 23 ] .…”
Section: Zugelassene Topische Therapienunclassified
“…Daher kann eine adäquate Behandlung der persistierenden Gesichtsröte die Lebensqualität verbessern . So konnte in einer 8‐tägigen multizentrischen, randomisierten Studie, in der Brimonidin 3 mg/g Gel mit einem Vehikel‐Gel verglichen wurde, erwiesen werden, dass Patienten mit einem von ihnen selbst als schwer eingestuftes Erythem mit Hilfe von Brimonidin ihre Gesichtsröte schnell unter Kontrolle bringen konnten .…”
Section: Zugelassene Topische Therapienunclassified